2014
DOI: 10.1387/ijdb.140322mt
|View full text |Cite
|
Sign up to set email alerts
|

Integrating developmental biology and the fossil record of reptiles

Abstract: Numerous new discoveries and new research techniques have influenced our understanding of reptile development from a palaeontological perspective. They suggest for example that transition from mineralized to leathery eggshells and from oviparity to viviparity appeared much more often in the evolution of reptiles than was previously thought. Most marine reptiles evolved from viviparous terrestrial ancestors and had probably genetic sex determination. Fossil forms often display developmental traits absent or rar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 94 publications
1
15
0
3
Order By: Relevance
“…All known Choristodera laid soft eggshells unlike A. vesicularis (Ji et al, 2006;Hou et al, 2009) or are suggested to be viviparous (Ji et al, 2010;Blackburn and Sidor, 2014). There is no report of rigid eggshells in Choristodera so far (Sander, 2012;Skawiñski and Tałanda, 2014). However, Stein et al (2019) opened a discussion that well-mineralized rigid eggshells might have been independently evolved from very thin calcified eggshells in different dinosaur clades.…”
Section: Potential Egg-layermentioning
confidence: 99%
“…All known Choristodera laid soft eggshells unlike A. vesicularis (Ji et al, 2006;Hou et al, 2009) or are suggested to be viviparous (Ji et al, 2010;Blackburn and Sidor, 2014). There is no report of rigid eggshells in Choristodera so far (Sander, 2012;Skawiñski and Tałanda, 2014). However, Stein et al (2019) opened a discussion that well-mineralized rigid eggshells might have been independently evolved from very thin calcified eggshells in different dinosaur clades.…”
Section: Potential Egg-layermentioning
confidence: 99%
“…Amniotes are characterized by the amniotic egg, which enables complete development of the animal outside an aquatic environment and consequently the invasion of different terrestrial habitats (Sumida and Martin, 1997;Laurin, 2010;Skawiski and Tałanda, 2014;Brocklehurst et al, 2018). With development inside the egg [or, secondarily, inside the mother's womb (Piñeiro et al, 2012a;Werneburg et al, 2016)], the larval stage is lost and more or less fully formed, adult-resembling hatchings leave the eggs ( Figure 1C).…”
Section: Ontogenetic Plasticitymentioning
confidence: 99%
“…Allerdings darf nicht vergessen werden, dass die Fossilisationsbedingungen im marinen Milieu durch anhaltende Sedimentationen meist günstiger waren als an Land und daher marine Lebewesen häufiger im Fossilbericht zu finden sind. Außengruppenvergleiche mit sehr ursprünglichen Landwirbeltieren belegen aber unzweifelhaft einen terrestrisch‐oviparen Ursprung der Sauropsiden .…”
Section: Viviparie Bei Marinen Reptilienunclassified
“…Im Laufe der Evolution der Meeresreptilien erkennt man auch eine Zunahme der Körpergröße der Jungtiere sowie eine Abnahme der Wurfgröße. Die Energie wurde also in das Heranreifen weniger, aber kräftigerer und damit überlebensfähigerer Jungtiere gesteckt (K‐Strategie) als bei den evolutiv früheren Formen (r‐Strategie) . Bei dem Mosasaurier Carsosaurus aus der Kreidezeit wurden eingerollte Föten im Mutterleib entdeckt, ein Hinweis auf Ovoviviparie.…”
Section: Geburt Mit Dem Schwanz Voranunclassified
See 1 more Smart Citation